Концепція Божого синівства (παῖδα κυρίου): лінгвістичний аналіз Муд 2:13б (Linguostylistic Studies, 2020)
This article discusses the concept of divine sonship (παῖδα κυρίου) in the Book of Wisdom, chapter 2, verse 13b from the linguistic, literary,and theological perspectives. In this verse, the Bible author uses the phrase “a child/son of God” to express the unique relationship a righteous person has with God and demonstrate the consciousness of belonging to the Lord by the Jewish populace in diaspora. The aim of this paper is to explore how the author, by describing the pivotal feature of the life of the righteous in Wis 2:13b, uses the Greek terminology of his time as a means to teach about the faith. Lexical-syntactical, historical-cultural, and theological analyses are used to interpret the concept of the divine sonship in the Book of Wisdom. The patrimony of the Old Testament is taken into consideration as well. The Book of Wisdom written by a Jewish author in Egyptian Alexandria between 30 BCE – 14 CE reflects biblical theological thought, yet Pseudo-Solomon uses the terminology relevant to a Hellenistic milieu where he lives. The author teaches a younger Jewish generation in diaspora about their own religious tradition. The Jewish youth born in diaspora was more interested in contemporary philosophical/cultural trends than in the tradition of the ancestors. To attract them, the religious mentors present the topic using the conceptual terminology of the time. The concept of the divine sonship articulates the idea of a privileged status of the Jews and at the same time a responsibility that this status requires. This privileged status is traced back to the Exodus story when Israel was chosen as God’s people. As the book was written in diaspora, it also reflects the challenges the Jewish community was facing at that time. It was vital for the older generation to teach the younger generation about their ancestors and their beliefs. At the same time, the Hellenistic settings required Pseudo-Solomon to write in language that the audience spoke and to use the terminology that would yield meaning. The father-son image helps to identify the close relationship between the God and his people, mutual responsibility, and affection.
Keywords: Book of Wisdom; Bible; righteous person; Hellenistic milieu; virtuous life; terminology